Composition, film, laminate, and optical member

By using a combination of chain silica fine particles, alkoxysilane hydrolyzed condensate and hydrophilic resin, the cracking and peeling of the porous silicon oxide film during cutting processing is solved, and the softness and opticality of the film are improved. Performance, suitable for optical applications of porous silicon oxide films.

CN119234019APending Publication Date: 2024-12-31MITSUBISHI CHEM CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380028878.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-22
Filing Date
2023-03-22
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing porous silicon oxide films are prone to cracking and peeling during cutting, affecting their adhesion and optical properties.

Method used

By adjusting the composition and structure of the composition, the film is improved and cracking and peeling during cutting is suppressed by using a composition containing chain silica fine particles, an alkoxysilane hydrolyzed condensate and hydrophilic resin.

Benefits of technology

The film stability and optical performance are improved during cutting processing, and high adhesion and excellent refractive index are provided, which are suitable for optical applications of porous silicon oxide films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005051236350000101
    Figure BDA0005051236350000101
  • Figure BDA0005051236350000231
    Figure BDA0005051236350000231
Patent Text Reader

Abstract

Provided are: a composition which is capable of obtaining a film that has high flexibility and in which the occurrence of cracking and peeling during dicing is suppressed; a film obtained from the composition; a laminate; and an optical member. The composition contains fine chain silica particles, an alkoxysilane hydrolysis-condensation product, and a hydrophilic resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composition, a film, a laminate and an optical member. Background Art

[0002] Porous silicon oxide films have low refractive index, transparency, electrical insulation and other characteristics, and are widely used in industry. In particular, in the application field that utilizes the low refractive index, research is being conducted on their practical application in anti-reflection films for electronic device displays, automotive panels, lighting fixtures, sunlight utilization devices, camera lenses, masks, glasses, etc., as well as in optical waveguides and optical fiber claddings.

[0003] For example, Patent Document 1 discloses a method for producing a binder solution for forming a silicon oxide thin film which has excellent substrate adhesion and is suitable for forming a porous silicon oxide thin film. In addition, a method for producing a coating solution for forming a silicon oxide thin film is proposed, namely, a binder solution for forming a silicon oxide thin film formed by subjecting a hydrolyzable silane compound to a hydrolysis and condensation reaction and mixing the binder solution for forming a silicon oxide thin film formed from the reaction product with silicon dioxide particles.

[0004] In addition, Patent Document 2 proposes a porous silicon oxide film having excellent anti-fogging properties.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2019-23269

[0008] Patent Document 2: Japanese Patent Application Publication No. 2021-182134 Summary of the invention

[0009] Problems to be solved by the invention

[0010] However, the porous silicon oxide films described in Patent Documents 1 and 2 may be cracked or peeled off when the porous silicon oxide film and the substrate are laminated and then cut.

[0011] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a composition capable of obtaining a film having high flexibility and in which cracking and peeling are suppressed during cutting, and a film, a laminate and an optical member obtained from the composition.

[0012] Means for solving problems

[0013] The present inventors have conducted intensive studies to solve the above problems and have found that a film of a composition containing chain silica fine particles, an alkoxysilane hydrolysis condensate and a hydrophilic resin has increased flexibility and can suppress cracking and peeling during dicing, thereby completing the present invention.

[0014] That is, the gist of the present invention is as follows.

[0015] [1] A composition comprising chain silica fine particles, an alkoxysilane hydrolysis condensate, and a hydrophilic resin.

[0016] [2] The composition according to [1] above, wherein the hydrophilic resin has a hydroxyl group.

[0017] [3] The composition according to [1] or [2], wherein the content of hydroxyl groups directly bonded to the main chain of the hydrophilic resin is 35 mol % or less.

[0018] [4] The composition according to any one of [1] to [3], wherein the content of the hydrophilic resin exceeds 1 part by mass based on 100 parts by mass of the total of the chain silica fine particles and the alkoxysilane hydrolysis condensate.

[0019] [5] The composition according to any one of [1] to [4], wherein the content of the alkoxysilane hydrolysis condensate is 5% to 30% by mass relative to 100% by mass of the total of the chain silica fine particles, the alkoxysilane hydrolysis condensate and the hydrophilic resin.

[0020] [6] The composition according to any one of [1] to [5], wherein the content of the chain silica fine particles is 60% to 90% by mass relative to 100% by mass of the total of the chain silica fine particles, the alkoxysilane hydrolysis condensate and the hydrophilic resin.

[0021] [7] The composition according to any one of [1] to [6] above, wherein the weight average molecular weight of the alkoxysilane hydrolysis condensate is 1,000 to 5,000.

[0022] [8] The composition according to any one of [1] to [7] above, wherein the average primary particle size of the chain-like silica fine particles is 5 nm to 100 nm.

[0023] [9] The composition according to any one of [1] to [8] above, wherein the average degree of polymerization of the hydrophilic resin is 200 to 2,000.

[0024]

[10] A film comprising the composition according to any one of [1] to [9] above.

[0025]

[11] A film comprising a hydrophilic resin and having a porosity of 10% to 80%.

[0026]

[12] The film according to

[10] above, which has a thickness of 3,000 nm to 20,000 nm.

[0027]

[13] The film according to

[10] or

[12] above, wherein the porosity of the film is 10% to 80%.

[0028]

[14] The film according to any one of

[10] to

[13] above, wherein the refractive index is 1.15 to 1.40.

[0029]

[15] The membrane according to any one of

[10] to

[14] above, wherein the pore size of the membrane is 0.1 nm to 50 nm.

[0030]

[16] A laminate comprising the film according to any one of

[10] to

[15] above and a substrate.

[0031]

[17] The laminate according to

[16] above, wherein the substrate is glass.

[0032]

[18] An optical member comprising the laminated body according to

[17] above.

[0033] Effects of the Invention

[0034] The composition of the present invention, as described above, has a structure containing chain-like silica fine particles, an alkoxysilane hydrolysis condensate, and a hydrophilic resin.

[0035] This makes it possible to provide a film or a laminate that has high flexibility and is able to suppress cracking or peeling during cutting. DETAILED DESCRIPTION

[0036] Hereinafter, the composition, film, and laminate of the present invention will be described in detail by giving examples thereof, but the present invention is not limited to the following description and can be implemented with appropriate modifications other than those exemplified below without impairing the gist of the present invention.

[0037] In addition, "to" in this specification is used to mean that the numerical values ​​described before and after it are included as a lower limit and an upper limit.

[0038] [Composition]

[0039] The components of the composition of the present invention are described in detail below.

[0040] The composition of the present invention contains chain silica fine particles, an alkoxysilane hydrolysis condensate and a hydrophilic resin.

[0041] By using the composition of the present invention to form a film as a formed body, it is possible to manufacture a film as a formed body. In addition, by laminating the film on a substrate, a laminate can be obtained. Thus, for example, the flexibility of the film is improved, and it is possible to suppress the occurrence of cracks and peeling when the laminate is cut according to the product size, so that a film having excellent adhesion to the substrate and bendability and having an excellent refractive index for optical purposes can be obtained.

[0042] The form of the composition of the present invention is not particularly limited, and may be a liquid or a solid. The following two forms are exemplified as representative forms.

[0043] (I) Coating liquid containing chain silica particles, hydrophilic resin, alkoxysilane hydrolysis condensate and solvent

[0044] (II) Film containing chain-like silica fine particles, a hydrophilic resin and an alkoxysilane hydrolysis condensate

[0045] [Chain-shaped silica particles]

[0046] Chain silica particles refer to particles in which a plurality of primary particles are directly bonded by chemical bonds such as siloxane bonds without passing through a joint containing other materials, and are continuously formed into a chain shape. The shape may be a shape extending in a straight line, or a shape bending in two or three dimensions. In addition, the chain silica particles are preferably particles in which, for example, silica particles having an average primary particle size of about 5 to 30 nm are continuously connected to have an average length of about 30 to 200 nm. Here, the shape of the chain silica particles can be observed using an electron microscope (SEM, etc.). The average primary particle size is a specific surface area (m 2 / g), and the value obtained by the formula of average primary particle size = (2720 / specific surface area). The average length can be measured by a dynamic light scattering method.

[0047] Such chain-like silica particles have larger interparticle spaces in a stacked state, so the refractive index of the film can be reduced. On the other hand, when only silica particles other than chain-like silica particles, such as spherical silica particles, are used, a large amount of spherical silica particles need to be matched in order to reduce the refractive index. At this time, the content ratio of the matrix structure other than the spherical silica particles becomes smaller, so the haze increases and the appearance is significantly reduced. In the present invention, by using chain-like silica particles, both low refractive index and excellent appearance can be taken into account.

[0048] The average primary particle size of chain-like silica particles is preferably 6 nm or more, more preferably 7 nm or more. By setting the average primary particle size of chain-like silica particles to 6 nm or more, the refractive index of the film can be reduced. On the other hand, the average primary particle size of chain-like silica particles is preferably 100 nm or less, preferably 50 nm or less, more preferably 30 nm or less. By setting the average primary particle size of chain-like silica particles to 100 nm or less, a film with a desired film thickness can be easily formed, the roughness of the film surface, light scattering can be reduced, and the haze can be reduced.

[0049] Specific examples of chain-like silica particles include “SNOWTEX (registered trademark)-OUP” (average length: 40 to 100 nm), “SNOWTEX (registered trademark)-UP” (average length: 40 to 100 nm), “SNOWTEX (registered trademark) PS-M” (average length: 80 to 150 nm), “SNOWTEX (registered trademark) PS-MO” (average length: 80 to 150 nm), “SNOWTEX (registered trademark) PS-S” (average length: 80 to 120 nm), “SNOWTEX (registered trademark) PS-SO” (average length: 80 to 120 nm), “IPA-ST-UP” (average length: 40 to 100 nm), “MEK-ST-UP” (average length: 40 to 100 nm), “PGME-ST-UP” (average length: 40 to 100 nm), and “Fine Cataloid” manufactured by Nissan Chemical Industries, Ltd. F-120" and other colloidal silica. As needed, it is sometimes preferred to use solvent-substituted silica. As commercially available dispersion media, methyl ethyl ketone, methyl isobutyl ketone, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, etc. are known, and these dispersion media can be appropriately changed to other components for use.

[0050] The content of chain silica particles is preferably 60% to 90% by mass relative to the total 100% by mass of chain silica particles, alkoxysilane hydrolysis condensation product and hydrophilic resin ("mass of chain silica particles" / "mass of chain silica particles + mass of alkoxysilane hydrolysis condensation product + mass of hydrophilic resin"). When the content of chain silica particles is 60% by mass or more, the void ratio in the film becomes larger, so the refractive index can be reduced. More preferably, it is 65% by mass or more, and particularly preferably 70% by mass or more. On the other hand, when the content is 90% by mass or less, the adhesion to the substrate and the mechanical strength of the film are further improved. More preferably, it is 85% by mass or less, and particularly preferably 80% by mass or less.

[0051] [Alkoxysilane hydrolysis condensate]

[0052] The alkoxysilane hydrolysis condensate contained in the composition of the present invention is a compound having a siloxane bond, and is a compound formed by hydrolysis and condensation of alkoxysilane. The method for producing the alkoxysilane hydrolysis condensate is not particularly limited, and the alkoxysilane hydrolysis condensate includes a hydrolyzable silane compound and a polymer of a hydrolyzable silane compound, and is usually produced using water and an organic solvent. The composition produced from the hydrolyzable silane compound, the polymer of the hydrolyzable silane compound, water and an organic solvent is referred to as a silicate oligomer.

[0053] The weight average molecular weight of the alkoxysilane hydrolysis condensate of the present invention is preferably 1,000 to 5,000. If the weight average molecular weight of the alkoxy hydrolysis condensate is 1,000 or more, the silicate oligomer containing the alkoxy hydrolysis condensate is not easy to gel, and the storage stability becomes good. It is more preferably 1,500 or more, and particularly preferably 2,000 or more. In addition, if it is 5,000 or less, the adhesion with the substrate becomes better, and cracking and peeling during cutting are suppressed. It is more preferably 4,000 or less, and particularly preferably 3,000 or less. This weight average molecular weight is equivalent to a polymer with an average degree of polymerization n of 2 to 100.

[0054] The weight average molecular weight is a value measured by gel permeation chromatography (GPC) under the following conditions.

[0055] Solvent: Tetrahydrofuran

[0056] Device Name: TOSOH HLC-8220GPC

[0057] Column: TOSOH TSKgel Super HM-N (2 columns) and HZ1000 (1 column) connected Column temperature: 40°C

[0058] Sample concentration: 0.01 mass%

[0059] Flow rate: 0.6ml / min

[0060] Calibration curve: PEG (calibration curve using a 4-point cubic approximation with molecular weights of 20,000, 4,000, 1,000, and 200)

[0061] The concentration of the alkoxy hydrolysis condensate in the silicate oligomer is preferably 15% by mass or less, more preferably 10% by mass or less, and particularly preferably 8% by mass or less. When the concentration of the alkoxy hydrolysis condensate is 15% by mass or less, the stability of the solution is improved, and the dispersibility when mixed with chain-like silica particles is further improved. On the other hand, from the aspect of the shape efficiency of the film, the concentration of the alkoxy hydrolysis condensate in the silicate oligomer is preferably 0.1% by mass or more, and more preferably 0.2% by mass or more.

[0062] Such a silicate oligomer is transparent, and the turbidity measured using a kaolin turbidity meter is usually 10 or less.

[0063] As the organic solvent contained in the silicate oligomer, a hydrophilic solvent is preferably used. As the hydrophilic solvent, there is no particular limitation, and alcohols such as methanol, ethanol, propanol, butanol, cellosolves such as ethyl cellosolve, butyl cellosolve, propyl cellosolve, and glycols such as ethylene glycol, propylene glycol, and hexylene glycol are generally used. These solvents may be used alone or in combination of two or more.

[0064] The content of the organic solvent in the silicate oligomer is not particularly limited, but is usually 40% by mass to 99% by mass.

[0065] The hydrolyzable silane compound is a silane compound having a hydrolyzable group such as an alkoxy group, an alkoxyalkoxy group, an acyloxy group, an aryloxy group, an aminooxy group, an amide group, a ketoxime group, an isocyanate group, or a halogen atom. As the hydrolyzable silane compound, monofunctional to tetrafunctional hydrolyzable silane compounds are known, depending on the number of hydrolyzable groups.

[0066] In the present invention, an alkoxysilane compound is preferably used as the hydrolyzable silane compound. Examples of the alkyl group of the alkoxy group (-OR) include lower alkyl groups such as methyl, ethyl, propyl, and butyl.

[0067] Representative examples of alkoxysilane compounds include dimethyldimethoxysilane (DMDMS), methyltrimethoxysilane (MTMS), tetramethoxysilane (TMOS), dimethyldiethoxysilane (DMDES), methyltriethoxysilane (MTES), tetraethoxysilane (TEOS), etc. Commercially available products of dimethyldimethoxysilane (DMDMS) are generally solutions having a purity of 99% by mass.

[0068] The polymer of hydrolyzable silane compound is formed by polymerizing (oligomerization) the above-mentioned monomer by condensation. In this reaction, first, silanol group (-Si-OH) is formed by the hydrolysis of alkoxy. Alcohol (R-OH) is generated simultaneously. Then, siloxane bond (-Si-O-Si-O-) is formed by (dehydration) condensation of silanol group, and this condensation is repeated to form siloxane oligomer. As the polymer of alkoxysilane compound, from the aspects of hydrolysis and condensation of alkoxy, preferably R is the polymer of tetramethoxysilane of methyl or R is the polymer of tetraethoxysilane of ethyl.

[0069] The structure of the polymer includes a linear, branched, cyclic, or network structure. When a polymer of tetraalkoxysilane is represented as having a linear structure, it is represented by the following general formula (I).

[0070] RO(Si(OR)2O)n R···(I)

[0071] In the general formula (I), R is an alkyl group, and n represents the degree of polymerization of the polymer. Generally, the polymer obtainable is a composition of polymers having different n values, and thus has a molecular weight distribution. It should be noted that the degree of polymerization is represented by the average n.

[0072] Sometimes, "silicon dioxide content" is used to represent the degree of polymerization of a tetrafunctional hydrolyzable silane compound such as tetraalkoxysilane or its polymer. "Silicon dioxide content" refers to the mass ratio of silicon dioxide (SiO2) generated by the compound, which is obtained by measuring the amount of silicon dioxide generated by stably hydrolyzing and calcining the compound. In addition, "silicon dioxide content" also represents the ratio of silicon dioxide generated relative to one molecule of the compound, which is a value calculated by the following general formula (II).

[0073] Silica content (mass) = degree of polymerization × molecular weight of SiO2 / molecular weight of the compound (II)

[0074] In the present invention, a polymer having a degree of polymerization n of usually 2 to 100, preferably 2 to 70, and more preferably 2 to 50 is used. It is convenient to use a commercially available polymer. As the degree of polymerization n increases, the molecular weight of the generated alkoxysilane hydrolysis condensate increases, the molecular weight distribution becomes wider, and the viscosity increases.

[0075] Examples of commercially available polymers of hydrolyzable silane compounds include MKC SILICATE MS51, MKC SILICATE MS56, MKC SILICATE MS57, and MKC SILICATE MS56S (all polymers of tetramethoxysilane) manufactured by Mitsubishi Chemical Corporation, methyl silicate 51 (a polymer of tetramethoxysilane), methyl silicate 53A, ethyl silicate 40, and ethyl silicate 48 manufactured by Colcoat, and ethyl silicate 40 and silicate 45 (all polymers of tetraethoxysilane) manufactured by Tama Chemical Industries, Ltd.

[0076] The alkoxysilane hydrolysis condensate of the present invention is preferably manufactured using a hydrolyzable silane composition comprising a bifunctional hydrolyzable silane compound and a polymer of the hydrolyzable silane compound and the content of the polymer of the hydrolyzable silane compound being 50% by mass or more. The ratio of the polymer in the hydrolyzable silane composition is preferably 70% by mass or more. If the ratio of the polymer in the hydrolyzable silane composition is 70% by mass or more, a branched, cyclic, or mesh-like structure can be appropriately formed in the reaction composition, and the adhesion of the film to the substrate is further improved. More preferably 75% by mass or more.

[0077] On the other hand, the ratio of the multimer in the hydrolyzable silane composition is preferably 90% by mass or less. When the ratio of the multimer in the hydrolyzable silane composition is 90% by mass or less, gelation is less likely to occur, and storage stability is further improved.

[0078] In addition, the ratio of the bifunctional hydrolyzable silane compound as a monomer in the hydrolyzable silane composition is preferably 10 mass % or more and 30 mass % or less. If the ratio of the bifunctional hydrolyzable silane compound is 10 mass % or more, the silicate oligomer containing the alkoxysilane hydrolysis condensate obtained is not easy to gel, and the preservation property is more excellent. On the other hand, if it is 30 mass % or less, the coating property during film formation is more excellent. This ratio is more preferably 25 mass % or less.

[0079] The conditions for the hydrolysis and condensation reaction are preferably those described in Japanese Patent Application Laid-Open No. 2021-182134. The reaction is carried out by continuously dropping an acid catalyst aqueous solution into a hydrophilic solvent solution in which the hydrolyzable silane composition is dissolved under stirring.

[0080] The content of the alkoxysilane hydrolysis condensate is preferably 5% to 30% by mass in terms of the total ratio of the chain silica particles, the alkoxysilane hydrolysis condensate and the hydrophilic resin ("mass of the alkoxysilane hydrolysis condensate" / "mass of the chain silica particles + mass of the alkoxysilane hydrolysis condensate + mass of the hydrophilic resin"). When the ratio of the alkoxysilane hydrolysis condensate is too small, the film-forming property of the film is reduced, and when the ratio of the alkoxysilane hydrolysis condensate is too large, the refractive index of the film increases. The content of the alkoxysilane hydrolysis condensate is more preferably 5 to 25% by mass, and further preferably 5 to 20% by mass.

[0081] [Hydrophilic resin]

[0082] The composition of the present invention contains a hydrophilic resin. The hydrophilic resin preferably used in the present invention refers to a resin having a solubility of 5% by mass or more in water, methanol and ethanol. When the solubility is 5% by mass or more, the affinity with chain silica particles and alkoxysilane hydrolysis condensate becomes better, the haze of the film becomes low, and the appearance is more excellent. The solubility is preferably 8% by mass or more, and more preferably 10% by mass or more.

[0083] Examples of the hydrophilic resin include natural polymers, water-soluble resins, and resin emulsions. Specific examples of the hydrophilic resin used in the composition of the present invention include natural polymers such as casein, soybean protein, starch, and gelatin.

[0084] As examples of water-soluble resins, as resins having a hydroxyl group as a hydrophilic structural unit, polyvinyl alcohol resins (PVA), cellulose resins (methylcellulose (MC), ethylcellulose (EC), hydroxyethylcellulose (HEC), carboxymethylcellulose (CMC), etc.), chitins, and starches can be cited. In addition, as resins having an ether bond, polyethylene oxide (PEO), polypropylene oxide (PPO), polyethylene glycol (PEG), and polyvinyl ether (PVE) can be cited. Moreover, as resins having an amide group or an amide bond, polyacrylamide (PAAM) and polyvinyl pyrrolidone (PVP) can be cited.

[0085] Examples of the resin emulsion include conjugated diene polymer emulsions such as styrene-butadiene copolymers and methyl methacrylate-butadiene copolymers, acrylic polymer emulsions, vinyl polymer emulsions such as ethylene-vinyl acetate copolymers, ester polymer emulsions, urethane polymer emulsions, olefin polymer emulsions, epoxy polymer emulsions, and vinylidene chloride polymer emulsions.

[0086] The hydrophilic resin of the present invention preferably has a hydroxyl group. By having a hydroxyl group, the affinity with chain silica fine particles and alkoxysilane hydrolysis condensate becomes better, the haze of the film becomes low, and the appearance becomes more excellent.

[0087] Examples of such hydrophilic resins include polyvinyl alcohol-based resins, cellulose-based resins (methyl cellulose (MC), ethyl cellulose (EC), hydroxyethyl cellulose (HEC), carboxymethyl cellulose (CMC), etc.), chitins, and starch.

[0088] The content of hydroxyl groups directly bonded to the main chain of the hydrophilic resin is preferably 35 mol% or less. When the content of the hydroxyl groups is within the above range, film-forming properties, film flexibility, and cutting properties become good.

[0089] The content of the hydroxyl group is more preferably 32 mol% or less, more preferably 30.8 mol% or less, and further preferably 30 mol% or less. On the other hand, the content of the hydroxyl group is preferably 5 mol% or more, more preferably 10 mol% or more, more preferably 11.6 mol% or more, further preferably 15 mol% or more, and particularly preferably more than 17.8 mol%. By making the content of the hydroxyl group 5 mol% or more, the haze of the film becomes low and the appearance is more excellent.

[0090] The hydroxyl content can be determined, for example, by 1 When the hydrophilic resin is a vinyl alcohol resin, the content of the vinyl alcohol structural unit (hereinafter, corresponding to formula (1)) can also be calculated from the saponification degree as the ratio of the hydroxyl group in the vinyl alcohol structural unit.

[0091] The content of the hydrophilic resin is preferably more than 1 part by mass in terms of the ratio to the total of the silica particles and the alkoxysilane hydrolysis condensate ("mass of the hydrophilic resin" / "mass of the silica particles+mass of the alkoxysilane hydrolysis condensate"). When the content of the hydrophilic resin is within the above range, the flexibility and cutting properties of the film are improved.

[0092] The content of the hydrophilic resin is more preferably 1.5 parts by mass or more, further preferably 2.0 parts by mass or more, and particularly preferably 2.5 parts by mass or more. In addition, the upper limit is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and particularly preferably 20 parts by mass or less. By making the content of the hydrophilic resin 30 parts by mass or less, the haze of the film becomes low and the appearance is more excellent.

[0093] The content of the hydrophilic resin is preferably 5% to 30% by mass in terms of the ratio ("mass of the hydrophilic resin" / "mass of the chain silica particles + mass of the alkoxysilane hydrolysis condensate + mass of the hydrophilic resin") relative to the total of 100% by mass of the chain silica particles, the alkoxysilane hydrolysis condensate and the hydrophilic resin. When the content of the hydrophilic resin is 5% by mass or more, the flexibility and cutting properties of the film become good. More preferably, it is 8% by mass or more, and particularly preferably, it is 10% by mass or more. On the other hand, when the content is 30% by mass or less, the haze of the film becomes low and the appearance is more excellent. More preferably, it is 25% by mass or less, and particularly preferably, it is 20% by mass or less.

[0094] [Polyvinyl alcohol resin]

[0095] The composition of the present invention can preferably use a polyvinyl alcohol resin as a hydrophilic resin. The polyvinyl alcohol resin contained in the composition of the present invention is not particularly limited in its specific structure as long as it has a vinyl alcohol structural unit represented by the following formula (1). It is typically obtained by saponifying a polyvinyl carboxylate obtained by polymerizing a vinyl carboxylate monomer such as vinyl acetate, but is not limited thereto.

[0096] [Chemistry 1]

[0097]

[0098] Examples of the polyvinyl alcohol resin include unmodified polyvinyl alcohol and modified polyvinyl alcohol resins. The modified polyvinyl alcohol resin may be a copolymer-modified polyvinyl alcohol resin synthesized by copolymerizing monomers other than vinyl ester monomers that provide polyvinyl alcohol structural units, or a post-modified polyvinyl alcohol resin obtained by appropriately modifying the main chain or side chain with a compound after synthesizing unmodified polyvinyl alcohol.

[0099] Examples of comonomers (unsaturated monomers) that can be used for copolymerization and modification of polyvinyl alcohol-based resins include olefins such as ethylene, propylene, isobutylene, α-octene, α-dodecene, and α-octadecene; hydroxyl-containing α-olefins such as 3-butene-1-ol, 4-pentene-1-ol, and 5-hexene-1-ol, and their acylate derivatives; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, maleic anhydride, itaconic acid, and undecenoic acid, or their salts; monoesters or dialkyl esters; Amides such as diacetone acrylamide, acrylamide, and methacrylamide; olefin sulfonic acids or their salts such as ethylene sulfonic acid, allyl sulfonic acid, and methallyl sulfonic acid; quaternary ammonium salts such as diallyldimethylammonium chloride and diallyldiethylammonium bromide; substituted vinyl acetates such as isopropenyl acetate and 1-methoxyvinyl acetate; allyl ethers having a poly(oxyalkylene) group such as polyethylene glycol allyl ether, methoxypolyethylene glycol allyl ether, polypropylene glycol allyl ether, and polyethylene glycol-polypropylene glycol allyl ether, etc.

[0100] In addition, as copolymer modified polyvinyl alcohol resins, polyvinyl alcohol resins having primary hydroxyl groups in the side chains can be cited. As such polyvinyl alcohol resins, for example, side chain 1,2-diol modified PVA resins obtained by copolymerizing 3,4-diacetoxy-1-butene, vinyl ethylene carbonate, glycerol monoallyl ether, etc.; polyvinyl alcohol resins having hydroxymethyl groups in the side chains obtained by copolymerizing and saponifying hydroxymethyl vinylidene diacetates such as 1,3-diacetoxy-2-methylenepropane, 1,3-dipropionyloxy-2-methylenepropane, and 1,3-dibutyryloxy-2-methylenepropane.

[0101] As a method for post-modification of the post-modified polyvinyl alcohol-based resin, there can be mentioned methods of subjecting unmodified polyvinyl alcohol or the above-mentioned modified polyvinyl alcohol-based resin to acetoacetate esterification, acetalization, carbamate esterification, etherification, grafting, phosphate esterification, oxyalkylene esterification, transesterification, etc. From the aspect of the flexibility of the film, a polyvinyl alcohol-based resin modified with caprolactone by transesterification is more preferred.

[0102] The content of the vinyl alcohol structural unit contained in the polyvinyl alcohol resin is preferably 30 to 90 mol%. When the content of the vinyl alcohol structural unit is 30 mol% or more, the flexibility and bendability of the film are improved, and the rupture and peeling during cutting are suppressed. It is more preferably 32 mol% or more, further preferably 35 mol% or more, and particularly preferably more than 46 mol%. On the other hand, when the content of the vinyl alcohol structural unit is 90 mol% or less, the dispersibility in the organic solvent is good, the thickening of the liquid is also suppressed, and the appearance of the obtained film becomes better. It is more preferably 85 mol% or less, and particularly preferably 80 mol% or less.

[0103] As the functional group contained in the polyvinyl alcohol-based resin, an oxyalkylene group, an acetoacetyl group, a carboxyl group, and a sulfinyl group are preferred. From the viewpoint of flexibility of the film, an oxyalkylene group is more preferred.

[0104] The average polymerization degree of the polyvinyl alcohol-based resin is not particularly limited, but is preferably 200 to 2,000. When the average polymerization degree is 200 or more, the flexibility and bendability of the film are further improved. On the other hand, when it is 2,000 or less, the dispersibility in the organic solvent is further improved.

[0105] Relative to the total of 100 parts by mass of chain-like silica particles and alkoxysilane hydrolysis condensation products, the content of polyvinyl alcohol resin is preferably more than 1 part by mass. The content of polyvinyl alcohol resin is more preferably more than 1.5 parts by mass, more preferably more than 2.0 parts by mass, and particularly preferably more than 2.5 parts by mass. In addition, its upper limit is preferably less than 30 parts by mass, more preferably less than 25 parts by mass, and particularly preferably less than 20 parts by mass. By making the content of hydrophilic resin less than 30 parts by mass, the haze of the film becomes low level and the appearance is more excellent. When the content of polyvinyl alcohol resin is less, the flexibility and bendability of the film are further improved, and the film rupture during cutting can be suppressed. The content of polyvinyl alcohol resin is more preferably more than 5 parts by mass, more preferably more than 6 parts by mass, and particularly preferably more than 8 parts by mass. On the other hand, when the content is more, the dispersibility in the organic solvent is good, the thickening of the liquid is also suppressed, and the appearance of the obtained film becomes good.

[0106] [membrane]

[0107] The first film of the present invention can be set to a film obtained using the composition of the present invention. The film obtained by applying the composition of the present invention, especially when used for optical purposes, is usually used as a film obtained by forming a coating on a transparent substrate. The film is a porous film with multiple pores. In addition, the surface of the film is preferably smooth, and the concave-convex height difference is preferably less than 5nm, more preferably less than 3nm, and particularly preferably less than 2nm.

[0108] The second film of the present invention can be a film containing a hydrophilic resin and having a porosity of 10% to 80%. The second film has high industrial utilization value due to its excellent cutting properties, low haze, and low refractive index. The second film of the present invention can utilize a film related to the first film of the present invention, and the common parts thereof are collectively described as the film of the present invention.

[0109] <Refractive Index>

[0110] The refractive index of the film of the present invention is usually 1.15 or more and 1.40 or less, and can be appropriately selected for use according to the purpose. When used for an anti-reflection film of a glass or plastic substrate, the refractive index is preferably 1.20 or more and 1.35 or less. When the film is formed into an anti-reflection film in a single layer, the minimum reflectivity can be infinitely close to 0% by selecting the refractive index of the film according to the refractive index of the substrate. When used for a total reflection film, the refractive index is preferably 1.25 or less, more preferably 1.20 or less, and particularly preferably 1.18 or less.

[0111] A lower refractive index is preferred because it can increase the proportion of light totally reflected at the interface between the transparent substrate and the film. However, on the other hand, since the porosity of the film increases, the mechanical strength of the film may decrease.

[0112] <Structure>

[0113] The structure of the film of the present invention is not particularly limited, and its pores are usually tunnel-shaped, independent pores connected to form a connecting hole, but the detailed pore structure is not particularly limited. In addition, by adjusting the pore size and void ratio, the refractive index, dielectric constant, and density can be adjusted. By adjusting them, in addition to being applicable to optical purposes, it can also be applied to various purposes. The pore size and void ratio can be adjusted by the composition and coating method of the film-forming coating liquid described later.

[0114] The pore size of the film of the present invention is not particularly limited, and the pore size is usually preferably 0.1 to 50 nm, more preferably 1 to 20 nm, and particularly preferably 2 to 10 nm. If the pore size is too large, it is sometimes not suitable for an anti-reflection film formed by a thin film of about 100 nm, for example, and defects are generated on the surface of the formed film, the surface concavity becomes larger, and the haze becomes larger due to light scattering, etc. In addition, due to the large number of defects, there is also a problem of reduced mechanical strength of the film.

[0115] The porosity of the film of the present invention is preferably 10 to 80%, more preferably 10 to 78%, more preferably 20 to 78%, more preferably 30 to 78%, and particularly preferably 30 to 70%. If the porosity is 10% or more, the flexibility and optical properties become better, while if it is 80% or less, the mechanical strength, haze, and surface smoothness become better.

[0116] The pore size of the film of the present invention can be measured by analyzing an image observed using a transmission electron microscope (TEM) or a scanning electron microscope (SEM).

[0117] The porosity of the film can be determined from a relationship between the porosity and the refractive index based on the Lorentz-Lorentz equation.

[0118] The thickness of the film of the present invention is preferably 50nm to 20,000nm. The thickness is more preferably 1,000nm or more, further preferably 2,000nm or more, and particularly preferably 3,000nm or more. When the thickness is 50nm or more, the optical effect is exerted, and the mechanical strength is also better. On the other hand, if it is 20,000nm or less, the structure of the film is easily uniform. It is more preferably 19,000nm or less, and particularly preferably 17,000nm or less. The thickness can be measured by the method described in the embodiments described later.

[0119] The haze of the film of the present invention is preferably 0 to 3.0%. The haze is more preferably 2.5% or less, further preferably 2.0% or less, further preferably 1.8% or less, and particularly preferably 1.0% or less. When the haze is 3.0% or less, the optical properties become better. The lower limit is most preferably 0%. The haze can be measured by the method described in the examples described below.

[0120] [Method for producing film]

[0121] Hereinafter, an example of the method for producing the film of the present invention will be described, but the method for producing the film of the present invention is not limited to the following method.

[0122] To form the film of the present invention, a coating liquid for film formation (corresponding to the composition of the present invention, hereinafter also referred to as "film-forming coating liquid") is applied to a substrate, and the obtained wet film is heated and dried to be cured.

[0123] The film-forming coating liquid is produced, for example, by adding chain silica fine particles and a hydrophilic resin to a silicate oligomer containing an alkoxysilane hydrolysis condensate, and may contain a solvent as appropriate.

[0124] (Method for producing film-forming coating liquid)

[0125] The film-forming coating liquid is produced by mixing a silicate oligomer containing an alkoxysilane hydrolysis condensate, chain silica fine particles, and a hydrophilic resin.

[0126] The film-forming coating liquid is adjusted to an appropriate concentration in consideration of the coating properties when applied to the substrate, the film thickness, smoothness, etc. The concentration adjustment is performed by adding the above-mentioned hydrophilic solvent, and the concentration adjustment can be performed before or after mixing the chain-like silica particles.

[0127] The chain silica particle concentration of the film-forming coating liquid is preferably 30% by mass or less, more preferably 25% by mass or less, particularly preferably 20% by mass or less, and most preferably 17% by mass or less. When the chain silica particle concentration is 30% by mass or less, the coating property is further improved, and a film with surface smoothness can be formed. On the other hand, from the aspect of the film formation efficiency of the film, the chain silica particle concentration of the film-forming coating liquid is preferably 1% by mass or more, more preferably 5% by mass or more.

[0128] The mixing ratio of the silicate oligomer including the hydrolysis condensate of alkoxysilane and the chain silica fine particles is not particularly limited as long as the pores of the film are not clogged when a film is formed using the obtained film-forming coating liquid.

[0129] When the proportion of silicate oligomer is too high, it is difficult to form pores during film formation, so it is difficult to form a porous film with excellent optical properties as the original purpose. On the other hand, when the proportion of silicate oligomer is too low, the bonding between chain-like silica particles becomes weak, so the mechanical strength is insufficient, or the adhesion with the substrate becomes low, so there is a possibility of damage or peeling due to the subsequent process or the use environment.

[0130] From such a viewpoint, when the silicate oligomer containing an alkoxysilane hydrolysis condensate is mixed with the chain silica fine particles, the mixing ratio of the chain silica fine particles and the alkoxysilane hydrolysis condensate is preferably chain silica fine particles:alkoxysilane hydrolysis condensate = 1:0.01 to 2 (mass ratio), particularly preferably 1:0.05 to 1 (mass ratio).

[0131] The content of the hydrophilic resin in the film-forming coating liquid is preferably 0.05% by mass or more, more preferably 0.1% by mass or more. When the content is 0.05% by mass or more, the flexibility and bendability of the film are further improved. On the other hand, it is preferably 10% by mass or less, more preferably 5% by mass or less. When the content is 10% by mass or less, the thickening of the liquid is suppressed, and the appearance of the obtained film becomes better.

[0132] The solvent contained in the film-forming coating liquid is water and / or an organic solvent. The solvent preferably contains a hydrophilic solvent. As the hydrophilic solvent, there is no particular restriction, and usually alcohols such as methanol, ethanol, propanol, butanol, cellosolves such as ethyl cellosolve, butyl cellosolve, propyl cellosolve, ethylene glycol, propylene glycol, hexylene glycol and the like are used. These solvents can be used only one, or two or more can be mixed. These solvents can use solvents from the dispersion of each raw material, etc., or can be mixed when preparing the film-forming coating liquid.

[0133] [Laminated body]

[0134] A film composed of the composition of the present invention can be laminated on a substrate to form a laminate.

[0135] The substrate laminated with the film can be a transparent substrate such as glass or plastic. The transparent substrate has high light transmittance at a certain specific wavelength and can be appropriately selected according to the purpose of using ultraviolet light, visible light, or infrared light. The specific wavelength is not limited to the range of visible light, but in the use of anti-reflection films for optical equipment such as lenses, displays, solar cells, solar power generation, building materials, and interior and exterior decoration of automobiles, it is preferred to have high transmittance to light with wavelengths in the visible light region. A substrate with a total light transmittance of more than 60% is usually used.

[0136] The thickness and shape of the substrate are not particularly limited, and the substrate may have scattering or haze, or may have fine irregularities on its surface, as long as they do not affect the performance of the film.

[0137] Examples of the plastic constituting the substrate include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), polyimide (PI), polymethyl methacrylate (PMMA), and cycloolefin polymer (COP).

[0138] The surface of the substrate may be subjected to a surface modification treatment or may not be subjected to a surface modification treatment, and either treatment may be applicable.

[0139] (Coating method)

[0140] The method for laminating a film on a substrate is preferably a coating method, and examples thereof include dip coating, spin coating, die coating, spray coating, gravure coating, roll coating, curtain coating, screen printing, and inkjet printing.

[0141] (Drying / Curing Method)

[0142] The wet film formed by coating the film-forming coating liquid on the substrate is dried to remove the solvent, and the drying temperature is usually 50 to 80° C., preferably using a hot air dryer, etc. The drying time is usually 1 to 10 minutes, preferably 1 to 5 minutes.

[0143] In addition, when the transparent substrate is plastic, in order to impart adhesion, as the curing treatment after the above drying, it is recommended to irradiate ultraviolet rays in the presence of oxygen. Ultraviolet rays include near ultraviolet rays (near UV, wavelength 200-380nm), far ultraviolet rays (far UV, wavelength 10-200nm) and extreme ultraviolet rays (extreme UV, wavelength 1-10nm), but far ultraviolet rays are usually effective. As the ray source of ultraviolet rays, for example, low-pressure mercury lamps, high-pressure mercury lamps, excimer ultraviolet (excimer UV) lamps, halide lamps, lasers, etc. can be cited. The irradiation time of ultraviolet rays is usually 1 second to 3 minutes.

[0144] When the transparent substrate is glass or the like, the curing treatment is preferably performed at 80° C. to 150° C., preferably using a hot air dryer or the like. The curing time is usually 1 minute to 60 minutes, preferably 1 minute to 30 minutes.

[0145] [Optical components]

[0146] The optical component of the present invention may include the laminate of the present invention. The laminate itself may be used as an optical component, or the laminate may be used as a part of an optical component. As the optical component of the present invention, diffractive optical elements (DOE), cladding materials such as optical fibers, optical waveguides, optical displays, AR glass, camera lenses, medical lenses, micro lenses, LiDAR, etc. may be cited.

[0147] The film of the present invention can be suitably used as an antireflection film, etc. The film of the present invention can be suitably used in displays, automobile panels, lighting lamps, sunlight utilization devices, camera lenses, masks, glasses, optical waveguides, etc. As optical applications, it can be suitably used in cladding materials such as diffractive optical elements (DOE), optical fibers, optical waveguides, optical displays, AR glass, camera lenses, medical lenses, microlenses, LiDAR, etc. Furthermore, it can also be suitably used as a component for improving the color tone / brightness of a display.

[0148] Example

[0149] Hereinafter, the present invention will be described in detail by way of examples. However, the present invention can be modified as appropriate within a range not impairing the gist of the present invention, and is not limited to the following examples.

[0150] The measurements of various physical properties in the examples were carried out according to the following methods.

[0151] [Average primary particle size of silicon dioxide fine particles]

[0152] The average primary particle size of the silica fine particles was calculated by the BET method.

[0153] [Refractive index, film thickness]

[0154] The refractive index and film thickness of the porous silicon oxide film stack (1) were calculated from the reflectance spectrum obtained using the "interference film thickness measuring device F20" manufactured by Filmetrics.

[0155] [Porosity]

[0156] The porosity of the porous silicon oxide film stack (1) was calculated from the relationship between the porosity and the refractive index based on the Lorentz-Lorentz equation. The refractive index of the silicon dioxide fine particles was 1.46.

[0157] (Lorentz-Lorentz formula)

[0158] Void ratio (%) = (refractive index of silica particles - refractive index of porous silica film) / 0.46

[0159] [Haze]

[0160] The porous silicon oxide film stack (2) was measured at room temperature using a spectroscopic colorimeter-haze meter ("COH7700" manufactured by Nippon Denshoku Industries).

[0161] [Film-forming properties]

[0162] The film-forming properties during film production were evaluated according to the following criteria.

[0163] ○: A uniform film having a film thickness of 2.0 μm or more can be produced without any problem.

[0164] ×: It is impossible to produce a film having a thickness of 2.0 μm or more.

[0165] [Cutting properties]

[0166] The porous silicon oxide film stack (2) was cut from the glass side at room temperature using a cutter with a diamond cutting grindstone ("Qcut150A" manufactured by QATM). The cross section after cutting was observed using FE-SEM ("JSM-7900F" manufactured by Nippon Denshi Co., Ltd.), and the film surface after cutting was observed using a laser microscope ("VK-9700" manufactured by KEYENCE Co., Ltd.), and evaluated according to the following criteria.

[0167] (rupture)

[0168] ○: There is no film breakage in cross-sectional observation.

[0169] ×: There is film breakage in cross-sectional observation.

[0170] (Peeling Evaluation Method 1)

[0171] ○: There was no film peeling in the surface observation.

[0172] ×: Film peeling was present in surface observation.

[0173] (Peeling Evaluation Method 2)

[0174] The porous silicon oxide film stack (2) was scratched from the glass side with a diamond cutter at room temperature, and force was applied evenly from both sides of the scratch. The surface of the film manually broken along the scratch was observed with a laser microscope ("VK-9700" manufactured by KEYENCE) and evaluated according to the following criteria.

[0175] ○: No film peeling was observed in the surface observation.

[0176] △: The film was partially peeled off in surface observation.

[0177] ×: Film peeling was present throughout in surface observation.

[0178] [Softness]

[0179] The porous silicon oxide film stack (3) was wound around a 1 mm Φ cylindrical metal rod at room temperature with the coating film surface facing upward, and the state of the test piece was observed and evaluated according to the following criteria.

[0180] ○: The film had no cracks or peeling.

[0181] ×: The film was cracked and the wound portion peeled off.

[0182] [Manufacturing Example 1] Manufacture of Silicate Oligomer (A) Containing Alkoxysilane Hydrolysis Condensate

[0183] (1) Hydrolysis reaction process:

[0184] In a 500 mL jacketed reactor, 5 parts by mass of "KBM22" (dimethyldimethoxysilane content 99% by mass) manufactured by Shin-Etsu Silicone Co., Ltd., 20 parts by mass of "Silicate MS51" (average degree of polymerization n: 7, methyl silicate oligomer content 99.8% by mass) manufactured by Mitsubishi Chemical Co., Ltd., and 50 parts by mass of ethanol were added, and the upper limit temperature of the reaction was set to 40°C. Under stirring conditions, 33 parts by mass of a 0.007% by mass aqueous solution of hydrochloric acid was added dropwise over 10 minutes. At this time, the reaction temperature rose by 5 to 10°C due to the exothermic reaction. Stirring was continued until the reaction temperature dropped by 5 to 10°C. It should be noted that the ratio of the multimer of the hydrolyzable silane compound in the total of the bifunctional hydrolyzable silane compound and the multimer of the hydrolyzable silane compound (the ratio of "Silicate MS51" to the total amount of "KBM22" and "Silicate MS51") was 80% by mass.

[0185] (2) Condensation reaction process:

[0186] After the aqueous hydrochloric acid solution was added dropwise, the temperature was raised to 60°C over 30 minutes with stirring, and the temperature was maintained at 60°C for 30 minutes, followed by cooling to room temperature.

[0187] (3) Condensation reaction stopping process:

[0188] After cooling, 108 parts by mass of ethanol was added and stirred for 30 minutes to obtain 216 parts by mass of silicate oligomer (A) containing alkoxysilane hydrolysis condensate. The concentration of alkoxysilane hydrolysis condensate contained in the obtained silicate oligomer (A) containing alkoxysilane hydrolysis condensate was 15%, and the weight average molecular weight was 1949.

[0189] [Production Example 2] Production of Silicate Oligomer (B) Containing Alkoxysilane Hydrolysis Condensate

[0190] 50 parts by mass of ethanol were added to 100 parts by mass of the silicate oligomer (A) containing an alkoxysilane hydrolysis condensate, and the mixture was stirred for 30 minutes to obtain 150 parts by mass of the silicate oligomer (B) containing an alkoxysilane hydrolysis condensate.

[0191] [Manufacturing Example 3] Manufacture of a coating liquid (C) for forming a porous silicon oxide film

[0192] 97 parts by mass of chain silica particles (“SNOWTEX OUP” manufactured by Nissan Chemical Industries, Ltd., average primary particle size: 12 nm, average length: 40 to 100 nm, silica particle concentration: 15 mass%) and 268 parts by mass of chain silica particles (“ORGANOSILICASOL MEK-ST-UP” manufactured by Nissan Chemical Industries, Ltd., average primary particle size: 12 nm, average length: 40 to 100 nm, silica particle concentration: 20 mass%) were added to 150 parts by mass of a silicate oligomer (B) containing an alkoxysilane hydrolysis condensate, and the mixture was stirred for 30 minutes to obtain 515 parts by mass of a coating solution (C) for forming a porous silicon oxide film.

[0193] [Example 1]

[0194] 3.75 parts by mass of oxyalkylene-modified polyvinyl alcohol (product "GOHSENX LW-100" manufactured by Mitsubishi Chemical Corporation, concentration 40% by mass, saponification degree 39-46 mol%, polymerization degree 200) was added to 100 parts by mass of the porous silicon oxide film-forming coating liquid (C), and stirred for 30 minutes to prepare 103.75 parts by mass of the porous silicon oxide film-forming coating liquid (D) of the present invention, and evaluated. The results are shown in Table 1.

[0195] [Example 2]

[0196] 107.50 parts by mass of a porous silicon oxide film-forming coating liquid (D) was prepared in the same manner as in Example 1 except that the amount of oxyalkylene-modified polyvinyl alcohol (product "GOHSENX LW-100" manufactured by Mitsubishi Chemical Corporation, concentration 40% by mass, saponification degree 39 to 46 mol%, polymerization degree 200) added was 7.50 parts by mass, and the results were shown in Table 1.

[0197] [Example 3]

[0198] 107.50 parts by mass of a porous silicon oxide film-forming coating liquid (D) was prepared in the same manner as in Example 1, except that 7.50 parts by mass of CL-modified PVOH (52 parts by mass of GOHSENOL NM-11Q manufactured by Mitsubishi Chemical Corporation, with a saponification degree of 99.1 mol%, a polymerization degree of 1200, and a caprolactone modification in the presence of a Lewis acid, and the resulting modified product was diluted with ethanol to 10 wt%) was used instead of oxyalkylene-modified polyvinyl alcohol (product "GOHSENX LW-100" manufactured by Mitsubishi Chemical Corporation, with a concentration of 40 mol%, a saponification degree of 39 to 46 mol%, and a polymerization degree of 200) was used, and the evaluation was performed. The results are shown in Table 1.

[0199] [Example 4]

[0200] 115.00 parts by mass of a porous silicon oxide film-forming coating liquid (D) was prepared in the same manner as in Example 1, except that 15.00 parts by mass of CL-modified PVOH (52 mol% of GOHSENOL NM-11Q (99.1 mol% by mass, 1200% by mass) manufactured by Mitsubishi Chemical Corporation was used instead of oxyalkylene-modified polyvinyl alcohol (product "GOHSENX LW-100" manufactured by Mitsubishi Chemical Corporation, concentration 40% by mass, saponification degree 39-46 mol%, polymerization degree 200) and the like, and the evaluation was performed. The results are shown in Table 1.

[0201] [Example 5]

[0202] 103.75 parts by mass of a porous silicon oxide film-forming coating liquid (D) was prepared in the same manner as in Example 1, except that 3.75 parts by mass of an oxyalkylene-modified polyvinyl alcohol (a product "GOHSENX LW-200" manufactured by Mitsubishi Chemical Corporation, a concentration of 40% by mass, a saponification degree of 39 to 46% by mass, and a polymerization degree of 200) was used instead of the oxyalkylene-modified polyvinyl alcohol (a product "GOHSENX LW-100" manufactured by Mitsubishi Chemical Corporation, a concentration of 40% by mass, a saponification degree of 46 to 53% by mole, and a polymerization degree of 200). The results are shown in Table 1.

[0203] [Example 6]

[0204] 104.50 parts by mass of a porous silicon oxide film-forming coating liquid (D) was prepared in the same manner as in Example 1, except that 4.50 parts by mass of polyvinyl alcohol (a product "GOHSENX LW-100" manufactured by Mitsubishi Chemical Corporation, concentration 40% by mass, saponification degree 46-53 mol%, polymerization degree 200) was used instead of oxyalkylene-modified polyvinyl alcohol (a product "GOHSENX LW-100" manufactured by Mitsubishi Chemical Corporation, concentration 40% by mass, saponification degree 46-53 mol%, polymerization degree 200) 4.50 parts by mass of the coating liquid was prepared and evaluated. The results are shown in Table 1.

[0205] [Example 7]

[0206] A coating liquid (D) for forming a porous silicon oxide film (107.50 parts by mass) was prepared in the same manner as in Example 5 except that 7.50 parts by mass of polyvinyl alcohol (product "GOHSENOL NK-05R" manufactured by Mitsubishi Chemical Corporation, concentration 10% by mass, saponification degree 71 to 75 mol%, polymerization degree 500) was used, and evaluation was performed. The results are shown in Table 1.

[0207] [Example 8]

[0208] A coating liquid (D) for forming a porous silicon oxide film of 115.00 parts by mass was prepared in the same manner as in Example 5 except that 15.00 parts by mass of polyvinyl alcohol (product "GOHSENOL NK-05R" manufactured by Mitsubishi Chemical Corporation, concentration 10% by mass, saponification degree 71 to 75 mol%, polymerization degree 500) was used, and evaluation was performed. The results are shown in Table 1.

[0209] [Comparative Example 1]

[0210] A porous silicon oxide film-forming coating liquid was prepared and evaluated in the same manner as in Example 1 except that no oxyalkylene-modified polyvinyl alcohol was added to the porous silicon oxide film-forming coating liquid (C).

[0211] [Comparative Example 2]

[0212] A porous silicon oxide film-forming coating liquid was prepared in the same manner as in Comparative Example 1, except that 340.75 parts by mass of spherical silica particles (a product "SNOWTEX OS" manufactured by Nissan Chemical Industries, Ltd., average primary particle diameter: 9 nm, average length: 40 to 100 nm, silica particle concentration 20% by mass) were diluted with 24.25 parts by mass of ethanol instead of 97 parts by mass of chain silica particles (a product "SNOWTEX OUP" manufactured by Nissan Chemical Industries, Ltd., average primary particle diameter: 12 nm, average length: 40 to 100 nm, silica particle concentration 15% by mass) and 268 parts by mass of chain silica particles (a product "ORGANOSILICASOL MEK-ST-UP" manufactured by Nissan Chemical Industries, Ltd., average primary particle diameter: 12 nm, average length: 40 to 100 nm, silica particle concentration 20% by mass) instead of 24.25 parts by mass of ethanol. The results are shown in Table 1. In addition, since Comparative Example 2 had problems in film forming properties and the like, the values ​​of the refractive index and the porosity could not be clearly determined, and therefore they are described as "not measured" in Table 1.

[0213] [Comparative Example 3]

[0214] A coating liquid (E) for forming a porous silicon oxide film was prepared in the same manner as in Preparation Example 3, except that 340.75 parts by mass of spherical silica particles ("SNOWTEX OS", a product manufactured by Nissan Chemical Industries, Ltd., average primary particle size: 9 nm, average length: 20% by mass of silica particles) were diluted with 24.25 parts by mass of ethanol instead of 97 parts by mass of chain silica particles ("SNOWTEX OUP", a product manufactured by Nissan Chemical Industries, Ltd., average primary particle size: 12 nm, average length: 40 to 100 nm, silica particle concentration: 15% by mass) and 268 parts by mass of chain silica particles ("ORGANOSILICASOL MEK-ST-UP", a product manufactured by Nissan Chemical Industries, Ltd., average primary particle size: 12 nm, average length: 40 to 100 nm, silica particle concentration: 20% by mass). Next, a porous silicon oxide film-forming coating liquid was prepared and evaluated in the same manner as in Example 6 except that the obtained porous silicon oxide film-forming coating liquid (E) was used instead of the porous silicon oxide film-forming coating liquid (C).

[0215] [Preparation of Porous Silicon Oxide Film Laminated Body (1) (for Evaluation of Refractive Index and Porosity)]

[0216] A 6-inch Si wafer (produced by Advance Materials Technology) was cut into 2 cm size, and the porous silicon oxide film-forming coating liquid obtained above was dropped thereon, and the film was coated at 3500 rpm for 30 seconds using a spin coater ("MS-A150" produced by MIKASA) to form a thin film.

[0217] Then, in order to remove the solvent and perform thermal curing, the film was placed in a low temperature constant temperature blower (manufactured by YAMATO Scientific Co., Ltd.) and dried at 120°C for 10 minutes, thereby obtaining a laminate (1) of a porous silicon oxide film and a Si wafer having a thickness of 3.5 μm. The refractive index and porosity of the obtained porous silicon oxide film laminate (1) were measured. The evaluation results obtained are shown in Table 1.

[0218] [Preparation of porous silicon oxide film stack (2) (for cutting and haze evaluation)]

[0219] The porous silicon oxide film-forming coating liquid obtained above was dropped onto a 1 mm thick slide glass plate ("S9111" manufactured by Matsunami Glass Co., Ltd.), and applied using a spin coater ("MS-A150" manufactured by Mikasa Co., Ltd.) at 2000 rpm for 30 seconds to prepare a thin film.

[0220] Then, in order to remove the solvent and perform thermal curing, the film was placed in a low temperature constant temperature blower (manufactured by YAMATO Scientific Co., Ltd.) and dried at 120°C for 10 minutes, thereby obtaining a laminate (2) of a porous silicon oxide film and a glass plate having a thickness of 4.5 μm. The obtained porous silicon oxide film laminate (2) was used to evaluate the cutting property and haze. The obtained evaluation results are shown in Table 1.

[0221] [Preparation of porous silicon oxide film stack (3) (for evaluation of flexibility)]

[0222] The porous silicon oxide film-forming coating liquid obtained above was dropped onto a 0.3 mm thick acrylic sheet ("Technolloy S000" manufactured by Sumika Acrylic Sales Co., Ltd.), and applied using a spin coater ("MS-A150" manufactured by Mikasa Corporation) at 2000 rpm for 30 seconds to prepare a thin film.

[0223] Then, in order to remove the solvent and perform thermal curing, the mixture was placed in a low temperature constant temperature blower (manufactured by YAMATO Scientific Co., Ltd.) and dried at 70°C for 10 minutes, thereby obtaining a laminate (3) of a porous silicon oxide film and an acrylic sheet having a thickness of 4.5 μm. The obtained porous silicon oxide film laminate (3) was used to evaluate the flexibility. The evaluation results obtained are shown in Table 1.

[0224] [Table 1]

[0225]

[0226] The results of this example show that the films and laminates comprising the compositions of the present invention described in Examples 1 to 8 have excellent flexibility and can suppress film breakage and peeling during cutting. In addition, the films have low refractive index and haze and excellent optical properties.

[0227] Since the film of Comparative Example 1 did not contain a hydrophilic resin in the composition, it was insufficiently flexible and cracked and peeled off during cutting.

[0228] The film of Comparative Example 2 used spherical silica particles instead of chain silica particles and did not contain a hydrophilic resin, and had poor film-forming properties, flexibility, and cutting properties. In addition, the film had high haze and poor optical properties.

[0229] Comparative Example 3 uses spherical silica particles instead of chain silica particles, and the film-forming property, flexibility, and cutting property are poor. In addition, the haze and refractive index of the film are high, and the optical properties are also poor. Furthermore, the porosity is low.

[0230] Possibility of Industrial Application

[0231] The porous silicon oxide film and laminate containing the composition of the present invention have high flexibility and can suppress cracking and peeling during cutting, so they can be suitably used in optical components such as diffractive optical elements (DOE), optical fiber cladding materials, optical waveguides, optical films, AR glasses, camera lenses, medical lenses, micro lenses, and LiDAR. In particular, they can be effectively used in applications that require miniaturization and tracking of components.

Claims

1. A composition comprising chain-like silica fine particles, an alkoxysilane hydrolysis condensate and a hydrophilic resin.

2. The composition according to claim 1, wherein The hydrophilic resin has a hydroxyl group.

3. The composition according to claim 1 or 2, wherein The content of hydroxyl groups directly bonded to the main chain of the hydrophilic resin is 35 mol % or less.

4. The composition according to any one of claims 1 to 3, wherein The content of the hydrophilic resin exceeds 1 part by mass based on 100 parts by mass of the total of the chain silica fine particles and the alkoxysilane hydrolysis condensate.

5. The composition according to any one of claims 1 to 4, wherein The content of the alkoxysilane hydrolysis condensate is 5% by mass to 30% by mass based on 100% by mass of the total of the chain silica fine particles, the alkoxysilane hydrolysis condensate, and the hydrophilic resin.

6. The composition according to any one of claims 1 to 5, wherein The content of the chain-like silica fine particles is 60% to 90% by mass based on 100% by mass of the total of the chain-like silica fine particles, the alkoxysilane hydrolysis condensate, and the hydrophilic resin.

7. The composition according to any one of claims 1 to 6, wherein The weight average molecular weight of the alkoxysilane hydrolysis condensate is 1,000 to 5,000.

8. The composition according to any one of claims 1 to 7, wherein The average primary particle size of the chain-like silica particles is 5 nm to 100 nm.

9. The composition according to any one of claims 1 to 8, wherein The average polymerization degree of the hydrophilic resin is 200 to 2,000. 10 . A film comprising the composition according to claim 1 .

11. A film comprising a hydrophilic resin and having a porosity of 10% to 80%.

12. The film according to claim 10 or 11, which has a thickness of 3,000 nm to 20,000 nm.

13. The film according to claim 10 or 12, wherein The porosity of the membrane is 10% to 80%. 14 . The film according to claim 10 , which has a refractive index of 1.15 to 1.

40.

15. The film according to any one of claims 10 to 14, wherein The pore size of the membrane is 0.1 nm to 50 nm. 16 . A laminate comprising the film according to claim 10 and a substrate.

17. The laminate according to claim 16, wherein The substrate is glass. An optical member comprising the laminate according to claim 17 .